The Main Activities of Think Tanks of the EAEU States - Vladimir Alexandrovich Shamakhov; Alexei Victorovich Vovenda; Petr Andreevich Koryagin (Управленческое консультирование, 2018)
In the article are characterized the key directions of activity of the expert-analytical centers (Think tanks) in the context of the development of modern trends of foreign economic strategies of the EEU’s states-partners.